1981
DOI: 10.1111/j.1748-1716.1981.tb06817.x
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on beta‐adrenergic control of transcapillary fluid absorption from skeletal muscle to blood during hemorrhage

Abstract: During hemorrhage fluid is absorbed from the extravascular space of skeletal muscle into the intravascular compartment in order to compensate for the blood loss. In a previous report (Lundvall & Hillman 1978) this process was found causally linked to reflex, beta-adrenergic control of the capillary hydrostatic pressure (via adjustment of pre-/postcapillary resistance) and of the capillary exchange area (via adjustment of "precapillary sphincter' tone). The present study extends the experimental evidence for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In cats, Hillman and colleagues found fluid replacement of 33% 10 min after 15% of the total blood volume was drained, and replacement of 66% after 45 min. However, it is clear that the rate of water shift depends on an adequate cardiovascular function [18,19]. In our investigation, 45% fluid replacement after removing 10% of the total blood volume took place during donation.…”
Section: Discussionmentioning
confidence: 70%
“…In cats, Hillman and colleagues found fluid replacement of 33% 10 min after 15% of the total blood volume was drained, and replacement of 66% after 45 min. However, it is clear that the rate of water shift depends on an adequate cardiovascular function [18,19]. In our investigation, 45% fluid replacement after removing 10% of the total blood volume took place during donation.…”
Section: Discussionmentioning
confidence: 70%
“…The experimental evidence indicated that activation of the /3-adrenoceptors, in the presence of a concomitant a-adrenergic constrictor influence, leads to decrease of capillary pressure as a result of a relatively more pronounced dilator interaction in post-than in pre-capillary resistance vessels and that the absorption process is further facilitated by /3-adrenergic relaxation of the precapillary 'sphincter' vessels leading to an increase in capillary surface area available for fluid exchange (Lundvall & Hillman 1978, Lundvall, Hillman & Gustafsson (1982. These microvascular effects in skeletal muscle evoked by activation of /32-adrenoceptors (Hillman & Lundvall 1981 a), are to some extent mediated by the sympathetic vasomotor fibres but mainly by catecholamines released from the adrenal medulla (Hillman & Lundvall 1981 b) and could be shown to be responsible for about 70% of the cumulated fluid absorption from skeletal muscle to blood (Hillman 1981).…”
mentioning
confidence: 99%
“…normovalaemia and unchanged mean arterial pressure, an increase in capillary surface area might result in increased transport of water and albumin, whereas during hypovolaemia and hypotension, e.g. during bleeding, the effect of P-adrenergic stimulation is the opposite, namely transport of water to the intravascular space (Hillmann, 1983).…”
Section: Plasma Volume Changes During Hypoglycaemiamentioning
confidence: 99%